Anz Line Resources / Nur Hasmira Hashim - Hashim, Nur Hasmira (2020)
Regarding this case study of Fundamentals of Entrepreneurship (ENT300) course requirement, I need to carry out a case study. During this case study, I need to collect some information about a company to complete this case study. So, I decided to interview the founder with a few questions through WhatsApp. From this interview, I get some information about entrepreneur profile, company background, organizational structure, product or service and business model.